2021
DOI: 10.36941/jesr-2021-0101
|View full text |Cite
|
Sign up to set email alerts
|

How does Online Formative Feedback Impact Student's Motivation and Self-Directed Learning Skills during the COVID-19 Pandemic?

Abstract: This research aims to prove the influences of online formative feedback on students' motivation and self-directed learning skills in the time of COVID-19. The questionnaire was sent to 645 students who have completed at least seven blended learning courses. They were asked to choose one class to describe the frequencies of assessment activities and their characteristics. The data was analyzed using SPSS and PLS software, showing that online feedback significantly positively impacts student motivation and self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…These learning tools are a number of materials, tools, media, instructions, and guidelines that will be used in the learning process [23]. Learning tools are very important for teachers because 1) they serve as guidelines in teaching and learning activities in the classroom, 2) serve as administrative equipment for increasing professionalism, and 3) make it easier for teachers to teach [24] and are able to improve their learning practices in the classroom [25]. The learning tools made by Indonesian language teachers in Buleleng Regency have shown the characteristics of 21 st century learning planning.…”
Section: B Discussionmentioning
confidence: 99%
“…These learning tools are a number of materials, tools, media, instructions, and guidelines that will be used in the learning process [23]. Learning tools are very important for teachers because 1) they serve as guidelines in teaching and learning activities in the classroom, 2) serve as administrative equipment for increasing professionalism, and 3) make it easier for teachers to teach [24] and are able to improve their learning practices in the classroom [25]. The learning tools made by Indonesian language teachers in Buleleng Regency have shown the characteristics of 21 st century learning planning.…”
Section: B Discussionmentioning
confidence: 99%
“…Some applications also already give the correct answers with a complete explanation. Hung (2021) found that integrating technology into assessments is a good solution during the pandemic. Students in VNU-University of Education showed that online assessment tools, such as Moodle, can increase students' and teachers' interaction and help them to give each other feedback immediately, especially in the discussion forums.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…En los últimos años, este proceso se ha efectuado con el soporte de las herramientas sincrónicas y asincrónicas de los entornos virtuales [16], [19]. De hecho, las investigaciones precedentes han destacado la efectividad de la retroalimentación mediada por herramientas tecnológicas para mejorar los resultados de aprendizaje de sus estudiantes [19], [20].…”
Section: B Retroalimentación Formativa: Proceso Dialógico Mediado Por...unclassified